Validation of three BRCA1/2 mutation-carrier probability models Myriad, BRCAPRO and BOADICEA in a population-based series of 183 German families - Schneegans, S. M. (Springer Netherlands, 2011)
Many studies have evaluated the performance of risk assessment models for BRCA1/2 mutation carrier probabilities in different populations, but to our knowledge very few studies have been conducted in the German population so far. In the recent study, we validated the performance of three risk calculation models by names BRCAPRO, Myriad and BOADICEA in 183 German families who had undergone molecular testing of mutations in BRCA1 and BRCA2 with an indication based on clinical criteria regarding their family history of cancer. The sensitivity and specificity at the conventional threshold of 10% as well as for a threshold of 20% were evaluated. The ability to discriminate between carriers and non-carriers was judged by the area under the receiver operating characteristics curve. We further focused on the performance characteristic of these models in patients carrying large genomic rearrangements as a subtype of mutations which is currently gaining increasing importance. BRCAPRO and BOADICEA performed almost equally well in our patient population, but we found a lack of agreement to Myriad. The results obtained from this study were consistent with previously published results from other population and racial/ethnic groups. We suggest using model specific decision thresholds instead of the recommended universal value of 10%. We further suggest integrating the CaGene5 software package, which includes BRCAPRO and Myriad, in the genetic counselling of German families with suspected inherited breast and ovarian cancer because of the good performance of BRCAPRO and the substantial ease of use of this software. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10689-011-9498-y) contains supplementary material, which is available to authorized users.